The impact of entrepreneurial education on technology-based enterprises development: The mediating role of motivation - Leo Paul Dana; Mehdi Tajpour; Salamzadeh Aidin; Elahe Hosseini; Mahnaz Zolfaghari (Administrative Sciences, 2021)
Technology-based enterprises play a paramount role in blooming a country economically. Nevertheless, according to a society's capacity to launch such enterprises in various eras, their volume is less than expected in many economies. Therefore, establishing such enterprises is necessary for developing any country, although its innovation system contributes to establishing them. This paper considers the impact of entrepreneurial education on technology-based enterprise development, including motivation as a mediator variable, in Esfahan Scientific and Industrial Town. Despite much research investigating the correlation between entrepreneurial education and technology-based enterprises' progress, it seems that no study has already considered this correlation with remarking the motivation as a mediator variable. This applied research follows a quantitative research design. The statistical population includes 500 enterprises in the Esfahan Scientific and Industrial Town, and for sampling, Cochran's formula was applied (n = 217). Additionally, the researcher-made questionnaire and PLS3 software were used for data gathering and analysis. The results demonstrated that entrepreneurial education elements (including entrepreneurial skill, entrepreneurial learning, and entrepreneurial intention) positively affect technology-based enterprises' development, considering motivation as a mediator variable. However, the impact of entrepreneurial intention on technology-based enterprises was not supported. It reveals that the entrepreneurial intention of motivated individuals could have a meaningful effect on the development of technology-based enterprises. Therefore, motivation is a critical issue to be considered by managers and policymakers while considering entrepreneurial education-related policies and initiatives.
Keywords: 350; development of technology-based enterprises; entrepreneurial education; entrepreneurial intention; motivation